Processos e camadas da música em rede - Felipe André Florentino Silva (2016)
This dissertation intends to verify the use of computer music and Internet networking technologies, such as the environment for the development of interactive musical composition systems distributed geographically. The chosen approach encompasses the data survey about multiplicity of tasks in production and performance ofnetwork music in an attempt to provide a comprehensive knowledge and providing autonomy to participants. The Telematic Art, generally lives by its own nature interdisciplinary fields. This work are discussed both the different approaches, classifications and concepts as the demands and functions in a music presentation Network, in order to provide a theoretical basis for the Networked Music. Also highlight the technological layers involving audio routing with computer netwoks, video transmission and monitoring of Internet connections. The research shows that by incorporate the barriers / resources from the network computing environment, we are faced with an emerging situation for composite and creative thinking in music where, as the traditional relations between musicians, space, composer, interpreter and audience are stressed.